Analysis of Vegetation and The Estimation of Carbon Stock in Indigenous Protected Forest Ghimbo Bonca Lida Kampar Riau - Remina, Dina; Chairul, Chairul; Nurainas, Nurainas (Metamorfosa: Journal of Biological Sciences, 2019)
Indonesia is one country that has the largest tropical forests in the world with an area of 133.69 million hectares of forest area. However, the presence of Indonesian forest threatened by deforestation and forest degradation. Efforts to overcome performed with the use of forests as providers of ecological and sink carbon. Analysis study conducted to determine the composition and structure of vegetation and carbon content in indigenous Protected Forest Ghimbo Bonca Lida, to obtain data on land use biomass part terraced plot (20x100 m) combined with traffic method. Carbon As for content used data allometric equation Kettering (2001) BK = 0.11 r D 2.62 . The result showed 76 species and 116 individuals belonging to 32 families. The dominant species on the level of the tree that is  Syzygium cf filiformis. Carbon stocks of plant life at the top of the Indigenous Protected Forest Ghimbo Bonca Lida at 23.864,72 kg/ha and the carbon stocks nekromass of 39.071,06 kg/ha. The total carbon stocks in the Indigenous Protected Forest Ghimbo Bonca Lida of 134.529,96 kg/ha or 134,53 ton/ha